2022
DOI: 10.3390/nu14091930
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Caffeine on Overall Performance in Basketball Players—A Systematic Review

Abstract: Caffeine supplementation has become increasingly popular among athletes. The benefits of caffeine include delaying the negative effects of fatigue, maintaining a high level of physical and mental performance, and improving certain abilities necessary for sport success. Given the complex nature of basketball, caffeine could be a legal, ergogenic stimulant substance, which will positively affect overall basketball performance. The purpose of this systematic review was to summarize evidence for the effect of acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…Caffeine can act as an adenosine antagonist [ 1 ], which reduces adenosine’s capacity to downregulate central nervous system arousal [ 60 ], and increase muscle fibers’ firing rates [ 61 ]. In contrast to the results of the present study, it has been reported that caffeine, when ingested prior to training sessions, could lead to significant but minor improvements in 10 m and 20 m sprinting performance in basketball players [ 7 ]. The above differences could be attributed to the fact that the effect of caffeine on athletes’ performance is not constant.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Caffeine can act as an adenosine antagonist [ 1 ], which reduces adenosine’s capacity to downregulate central nervous system arousal [ 60 ], and increase muscle fibers’ firing rates [ 61 ]. In contrast to the results of the present study, it has been reported that caffeine, when ingested prior to training sessions, could lead to significant but minor improvements in 10 m and 20 m sprinting performance in basketball players [ 7 ]. The above differences could be attributed to the fact that the effect of caffeine on athletes’ performance is not constant.…”
Section: Discussioncontrasting
confidence: 99%
“…Acute caffeine consumption improves jumping performance by enhancing athletes’ ability to produce greater peak force and rate of force development during a counter-movement jump [ 59 ]. Indeed, Lazić et al [ 7 ], in a recent meta-analysis, reported that the consumption of caffeine seems to be effective in the acute improvement of vertical jump performance in basketball players. On the other hand, it appears that acute consumption of creatine, β-alanine, citrulline malate or BCAAs has little to no influence on peak force and rate of force development in the absence of chronic loading or acute consumption associated with jumping height [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ergogenic effect of caffeine could appear when consumed in doses of 3-6 mg/kg body mass [10,11]. Moreover, it is suggested that 60 min pre-exercise could be the optimal timing due the plasma concentration peak [12].…”
Section: Introductionmentioning
confidence: 99%